RANCANG BANGUN ALAT PEMANGGANG SATE OTOMATIS DENGAN METODE PWM BERBASIS MIKROKONTROLER - Nababan, Ricky Yohanes; Sulindawaty, Sulindawaty (Majalah Ilmiah Kaputama, 2020)
In general, in grilling satay that we often encounter with satay traders or both in grilling for personal consumption, the fan is one of the manual tools used to fan the temperature of the embers to remain stable and reverse the satay also by manual means, with This method is often found in the level of maturity of the satay less evenly and there are some of them burnt satay so it is not effective and efficient in terms of time and material. From some of these cases an automatic satay roasting system appears, in maximum performance such as a fan that rotates automatically to maintain the stability of the embers with the temperature detected by the LM35 sensor so that the temperature remains monitored stable when roasted and processed by the motor Stepper as a satay turning player with the rotation adjusted to the temperature of the embers. Stepper motor with stable rotation is used PWM (Pulse Width Modulation) technique which is set by Microcontroller to control the fan, Stepper Motor, and LM35 sensor.